(untitled) (Plant Tissue Culture and Biotechnology, 2016)
Carrot (Daucus carota) is a valuable plant with both therapeutic and horticultural potential. Stem, petiole and root derived calli of carrot were obtained on solid MS supplemented with 1 mg/l BAP + 2 mg/l NAA. Callus cultures supplemented with different L-phenylalanine (PHE) concentrations under light and dark conditions were evaluated for their antioxidant activity and total phenolic contents. The authors showed that PHE supplementation in Daucus carota cultures was necessary to raise the extraction yield percentage. Antioxidant assays such as DPPH scavenging activity and ?-carotene bleaching have been carried out. In DPPH system, callus extracts from different explants grown under light conditions displayed lower DPPH radical scavenging activity at all PHE levels compared with that grown under dark conditions. Moreover, under both light and dark conditions callus cultures grown on MS supplemented with 1 mg/l BAP + 2 mg/l NAA plus 1000 mg/l PHE were recorded to yield the maximum values as antioxidant activities. Regarding ?-carotene bleaching assay, under light condition the callus extract of stem, root and petiole recorded an inhibition of linolic acid 47.9, 41.43 and 39%) which is lower compared with dark grown cultures, respectively (52.46, 72.71 and 73.26%). Effect of different concentrations of phenylalanine on the total phenolic content of carrot callus extract examined under light conditions varied from 0.33 to 2 mg/g DW and 0.51 to 3.69 mg/g DW under dark conditions as expressed Plant Tissue Cult. & Biotech. 25(2): 207-221, 2015 (December)